Perancangan Alat Bantu Angkat Beam Tenun Untuk Mengurangi Risiko Musculoskeletal Disorders (MSDS) Pada Departemen Weaving PT Sekar Lima Pratama - Rian Adi Prasetyo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Industry is an effort to produce finished goods using raw materials or raw materials through a manufacturing process in large quantities so that these goods can be obtained at the lowest possible price but with the highest quality (Made Sandi (2010: 148)). PT Sekar Lima Pratama is a textile industry that makes gray cloth which is raw cloth. This type of fabric cannot be sewn directly because it still contains starch which makes the fabric still rough. In the weaving section there were complaints related to the process of transporting woven blocks into the block delivery cart. The complaint that often arises is back pain after lifting the weaving block to place the cart that carries the block to the weaving location.